The Influence of Shopping Motivation, Self-Concept, and Reference Groups on the Consumptive Behavior of Generation Z Followers @discountfess - D.Salsabela Zein; Maulida Nurhidayati (Niqosiya: Journal of Economics and Business Research, 2026)
The development of digitalization and social media increases people's consumptive behavior through easy access to discount promotions. This phenomenon can be seen in @discountfess autobase accounts on platform X that share promo and discount information. This study aims to analyze the influence of shopping motivation, self-concept, and reference groups on the consumptive behavior of @discountfess followers. This study uses a quantitative method with an associative approach. The sampling technique used purposive sampling with a total of 100 @discountfess followers. The data were analyzed using multiple linear regression with the help of SPSS version 22. The results of the study showed that shopping motivation did not have a significant effect on consumptive behavior. Meanwhile, self-concept and reference groups have a significant positive effect on consumptive behavior. Simultaneously, shopping motivation, self-concept, and reference groups had a significant effect on consumptive behavior with an R Square value of 0.740.